Public stockholding programs and the WTO - Glauber, Joseph W. (International Food Policy Research Institute, 2024)
The issue of how support for public stockholding (PSH) programs is calculated and disciplined within the WTO Agreement on Agriculture (AoA) has been a point of contention since 2012. PSH was largely uncontroversial during the Doha negotiations, where issues like the Special Safeguard Mechanism, domestic support, and cotton contributed to the collapse of negotiations in 2008 (Blustein 2009; Jones 2010; Margulis 2023). However, members who raised administered prices to keep up with surging market prices in the late 2000s found themselves facing potential challenges, as support levels for PSH programs threatened to exceed domestic support commitments under the AoA.